2017
DOI: 10.1016/j.jcrs.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of femtosecond laser–assisted cataract surgery versus conventional phacoemulsification surgery for hard nuclear cataracts

Abstract: Compared with conventional phacoemulsification, femtosecond laser-assisted cataract surgery for hard nuclear cataracts conserved phacoemulsification power, provided a significant reduction in corneal endothelial damage, and led to faster visual rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 13 publications
3
54
0
3
Order By: Relevance
“…The regenerative properties of the endothelium are under debate, 18 yet clinically endothelial cell damage after cataract surgery can be permanent. 19 Therefore, putative corneal endothelial cell toxicity was determined for potential antiproliferative drugs.…”
mentioning
confidence: 99%
“…The regenerative properties of the endothelium are under debate, 18 yet clinically endothelial cell damage after cataract surgery can be permanent. 19 Therefore, putative corneal endothelial cell toxicity was determined for potential antiproliferative drugs.…”
mentioning
confidence: 99%
“…Our case had cataract surgery 6 years after ICL implantation. Compared with conventional phacoemulsification surgery, the FLACS is a safer and more precise surgery with advantages including more accurate capsulotomy, less corneal endothelial cell loss as well as better and faster visual rehabilitation [1,2,15]. Parkhurst et al and Li S. et al indicated the efficacy and safety of FLACS in cataract patients with ICLs [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The use of femtosecond lasers in cataract surgery has become commonplace, expanding from common cases to complicated cases [1][2][3]. Special cases have been reported in which the femtosecond laser has been used in cataract patients who have implantable collamer lenses (ICLs) in situ [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In post-LASIK eyes, postoperative corneal edema after cataract surgery may accumulate in the flap interface and the flap itself, causing early transient central corneal steepening and consequent myopic shift that could disappear after the corneal edema resolves [ 1 ]. However, the incidence of this complication could be reduced by FSL assisted lens fragmentation, which helps reduce phacoemulsification energy requirements, protect corneal endothelial cells, and thus shorten the recovery period and improve visual outcomes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%